Integrating neuromarketing into brand trust building strategies in the digital environment - Tkachova, Yaryna (Актуальні питання економічних наук, 2025)
The relevance of studying the theoretical and applied aspects of neuromarketing tools in brand promotion stems from the rapid digitalization of business processes, the growing importance of the emotional factor in consumer decision-making, and the diminishing effectiveness of traditional marketing approaches. The purpose of the article is to explore ways to integrate neuromarketing technologies into the strategy for building trust in brands in the digital environment and to formulate practical recommendations for their effective implementation in the activities of enterprises. Methods.The research methodology is based on an interdisciplinary approach that combines economic analysis, content analysis of modern neuromarketing methods, and a comparative review of domestic and foreign developments. Results. During the research process, it was established that up to 95% of consumer decisions are made subconsciously; therefore, neuromarketing provides unique opportunities for accurately identifying unconscious motives and predicting reactions to brand stimuli. Key neurotechnologies are systematized, and their ability to form an emotional response, which is the basis of consumer trust and loyalty, is shown. The practices of personalization, omnichannel interaction, content visualization, and emotional storytelling, which enhance the effect of neuromarketing approaches, were analyzed. It was found that the combination of emotional engagement with conscious cognitive confirmations of brand reliability ensures long-term customer loyalty. Based on international experience and Ukrainian market characteristics, a set of recommendations was developed that covers ethical standards for working with neurodata, developing the competencies of marketing teams, and implementing personalization and analytics to measure the level of consumer trust in the brand. Conclusions. The scientific novelty of the study lies in substantiating a comprehensive approach to integrating neuroanalytics, digital communications, and ethical principles into brand strategy. The practical significance lies in the application of the developed recommendations by enterprises in various industries to create long-term relationships with consumers, increase competitiveness, and promptly identify risks of loss of trust. The proposed approach can also serve as the basis for further research into the quantitative measurement of trust levels and the development of operational neuroanalytic tools.